Loser66
  • Loser66
Find all values of z such that z^4 = -4 Please, help
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Loser66
  • Loser66
@ganeshie8
Loser66
  • Loser66
\(z = |z|e^{i\theta}\) \(z^4 = |z|^4 e^{4i\theta} = -4 = 4e^{i\pi }\) Hence \(|z|^4 = 4 \rightarrow |z|=\sqrt2\) \(4i\theta = i(\pi+2k\pi) : k\in \mathbb Z\) then \(\theta = \pi/4 + k\pi/2\), Now I stuck. what is k?
freckles
  • freckles
\[-1=\cos(\pi+2 k \pi)+i \sin(\pi+2 k \pi) \\ -4=4e^{ \pi+2 k \pi} \\ z^4=4 e^{\pi+2k \pi} \\ \text{ now we want 4 roots } \\ \text{ so } k=0,1,2,3\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Loser66
  • Loser66
yes, I am crazy.This is what I did if k =0, then \(z = \sqrt2 e^{\pi/4}= \sqrt2(cos (\pi/4) + isin(\pi/4))= 1+i\) but then z^4 =(1+i)^4 from this I take |1+i| to get \sqrt 2, then ^4 and get 4, not -4. That throws me off. Thanks @freckles
Loser66
  • Loser66
@Crazy_questions senior in University.
anonymous
  • anonymous
grade is it 10th?
Loser66
  • Loser66
I have another question, @freckles
freckles
  • freckles
\[(1+i)^4=(1+i)^2(1+i)^2=(1+2i+i^2)(1+2i+i^2) \\ (1+i)^4=(2i)(2i)=4i^2=-4\]
Loser66
  • Loser66
\(|\dfrac{(2 + 3i)^4}{3-i)^2}|= \dfrac{|(2+3i)^4|}{|(3-i)^2|} =\dfrac{|2+3i|^4}{|3-i|^2}\)
Loser66
  • Loser66
Can I do that? since \(|2+ 3i| = \sqrt{4+(3)^2} = \sqrt{13} \) and \(|3-i|= \sqrt{3^2 + (-1)^2} = \sqrt {10}\)
Loser66
  • Loser66
If I can do that, then I can save my time
Loser66
  • Loser66
you see what the wolfram does. It takes a very long process to get my answer http://www.wolframalpha.com/input/?i=evalulate+|%282%2B3i%29^4%2F%283-i%29^2|
freckles
  • freckles
yes I believe that is right I was going to try to prove: \[|(a+bi)^n|=|a+bi|^n\] but the way I was going about it was taking too long
freckles
  • freckles
well I don't have the wolfram plus or whatver it is call to see what they have
freckles
  • freckles
or did
Loser66
  • Loser66
You can access to it free up to 3 problems
freckles
  • freckles
they expanded first right?
Loser66
  • Loser66
yea
Loser66
  • Loser66
I tested many times. They did what I did.
Loser66
  • Loser66
I have class in 15 minutes, still have many questions need help. Would you mind to help me out while I am not here ?
freckles
  • freckles
\[|(re^{i \theta})^n|=|r^n| |e^{i \theta n}| \\ \ \text{ assume } r>0 \\ \text{ then } |r^n|=r^n \\ \\ |(r e^{i \theta})^n|=r^n |e^{i \theta n}|=r^n| \cos(\theta n)+ i \sin(\theta n)| \\ =r^n \sqrt{\cos^2(\theta n )+ \sin^2(\theta n)} =r^n \\ |r e ^{i \theta}|^n=|r|^n |e^{ i \theta}|^n =r^n |e^{i \theta}|^n \text{ still assuming } r>0 \\ |r e ^{ i \theta}|^n=r^n (\sqrt{\cos^2(\theta)+\sin^2(\theta)})^n=r^n(1)^n=r^n\]
freckles
  • freckles
\[|a+bi|^n=|(a+bi)^n| \text{ seems to hold }\]
Loser66
  • Loser66
I have to go right now. Thanks @freckles

Looking for something else?

Not the answer you are looking for? Search for more explanations.